Effect of Different Coloring Procedures on the Aging Behavior of Dental Monolithic Zirconia - Check Agingu; Neng-wu Jiang; Hui Cheng; Hao Yu (Journal of Spectroscopy)
Objective. This study aimed to investigate the effect of different coloring procedures on the aging behavior of dental monolithic zirconia. Methods. Two types of translucent zirconia (SuperfectZir HTS, Aidite; Katana HT, Kuraray) were tested. Bar-shaped specimens with dimensions of 22 × 4 × 2 mm were prepared from uncolored and precolored blocks. Before being sintered, specimens made from uncolored blocks were colored by dipping them into a coloring liquid, whereas the precolored specimens were not treated. The specimens were then divided into 4 subgroups (n = 13) according to the aging conditions (no aging, 134°C/0.2 MPa for 5 h, 134°C/0.2 MPa for 10 h, and 134°C/0.2 MPa for 20 h). The flexural strength of the specimens was tested with the 4-point flexure. The crystalline phase composition of the specimens was analyzed by XRD. The subsurface microstructure of the fractured specimens was examined by using a SEM. The data were statistically analyzed using 3-way ANOVA and Tukey’s test (α = 0.05). Results. Significant differences were found in the flexural strength between the two zirconia materials tested (P<0.001). Aging and coloring procedures showed no significant effect on the flexural strength of the zirconia. Aging and coloring procedures significantly affected the t→m transformation of the zirconia. The monoclinic phase increased with the aging time. After aging, the precolored specimens showed a significantly higher t→m transformation than the specimens that were dipped in the coloring liquids. After aging for 20 h, the depth of the transformed zone with an irregular surface was approximately 6 µm for SuperfectZir HTS, whereas no detectable transformation zone was observed for Katana HT. Conclusion. Aging and coloring procedures had no significant effects on the flexural strength of the zirconia tested. The coloring procedure had a significant effect on the phase transformation of the zirconia subjected to hydrothermal aging.